Perbandingan Pendapatan Usahatani Bawang Merah Dengan dan Tanpa Teknologi Feromon (Studi Kasus di Gapoktan Asta Mandiri, Desa Songan B, Kecamatan Kintamani, Kabupaten Bangli) - SWASTIKA, KETUT; AMBARAWATI, I GUSTI AGUNG AYU; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
The Comparison of Shallot Farming Income by Using and without Pheromone Technology (Case Study at the Association of Asta Mandiri Farmer Groups,Songan B Village, Kintamani District, Bangli Regency) The main problem faced by farmers in shallot cultivation is the pest attack fromworms. Farmers mostly control the pest by using high doses of chemical insecticidespraying. Pheromone technology is a breakthrough technology that can be used tocontrol worm pest in shallot farming, heading to less use of insecticides. Thisresearch took place at the Association of Asta Mandiri Farmer Groups, Songan BVillage, Kintamani District, Bangli Regency which was conducted from April toMay 2016. The purpose of this study was to compare the shallot farming incomeusing pheromone technology and without pheromone technology and the obstaclesfaced by farmers in applying the technology. Data were analyzed using analysis offarm income, the R/C ratio, and t-test. The results showed that the income of shallotfarming with pheromone technology was at Rp 97,597,413.38 per hectare per season,whereas without pheromone technology at Rp 78,605,563.89 per hectare perseason.The R/C ratio of shallot farming by using pheromones technology was 2,39,whereas without the pheromone technology was 2,06. Based on t-test analysis, thereis significantly difference in income at 95% level of confidence. Obstacles faced byfarmers in applying pheromone technology, namely difficulties to obtain thepheromones in the market. It is expected that the government will provide thepheromones massively, so that farmers are able to apply the technology sustainably.
Keywords: farmincome; pheromone technology; obstacles; shallot